Quality of Life, Depression, and Healthcare Resource Utilization among Adults with Type 2 Diabetes Mellitus and Concomitant Hypertension and Obesity: A Prospective Survey - Andrew J. Green; Debbra D. Bazata; Kathleen M. Fox; Susan Grandy (Cardiology Research and Practice)
Background. This study compared quality of life, depression, and healthcare resource utilization among adults with type 2 diabetes mellitus (T2DM) and comorbid hypertension (HTN) and obesity with those of adults reporting T2DM alone. Methods. Respondents to the US SHIELD survey self-reported their height, weight, comorbid conditions, hospitalizations, and outpatient visits and completed the Short Form-12 (SF-12) and Patient Health Questionnaire (PHQ-9). Respondents reporting T2DM and HTN and obesity (body mass index, BMI, ≥30 kg/m2) were compared with a T2DM-alone group. Results. Respondents with T2DM, HTN, and obesity (n=1292) had significantly lower SF-12 Physical and Mental Component Summary scores (37.3 and 50.9, resp.) than T2DM-alone respondents (n=349) (45.8 and 53.5, resp., P<0.0001). Mean PHQ-9 scores were significantly higher among T2DM respondents with comorbid HTN and obesity (5.0 versus 2.5, P<0.0001), indicating greater depression burden. Respondents with T2DM, HTN, and obesity had significantly more resource utilization with respect to physician visits and emergency room visits but not hospitalizations than respondents with T2DM alone (P=0.03). Conclusions. SHIELD respondents with comorbid conditions of T2DM, HTN, and obesity reported greater healthcare resource utilization, more depression symptoms, and lower quality of life than the T2DM-alone group.